2020
DOI: 10.3171/2020.3.peds19574
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of large sylvian arachnoid cysts: the role of surgery has been exaggerated

Abstract: OBJECTIVEThe surgical indications for some arachnoid cysts (ACs) are controversial. While surgical procedures can be effective when an AC is a definite cause of hydrocephalus or papilledema, most ACs do not cause any symptoms or signs. Some surgeons perform several procedures to treat ACs because of their large size. The purpose of this study was to compare the long-term outcomes of Galassi type III ACs between surgery and nonsurgery groups. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…It has been shown that AC >5 cm is associated with cyst rupture or hemorrhage [30]. For these MFACs, some researchers believe that they should be operated on for their mass effect [29], while others argue that surgery may hurt rather than help the cognitive function of asymptomatic patients, especially young children [6]. Recently, more evidence has shown that MFACs have a negative effect on general cognitive ability and that this impairment can be improved by surgery [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that AC >5 cm is associated with cyst rupture or hemorrhage [30]. For these MFACs, some researchers believe that they should be operated on for their mass effect [29], while others argue that surgery may hurt rather than help the cognitive function of asymptomatic patients, especially young children [6]. Recently, more evidence has shown that MFACs have a negative effect on general cognitive ability and that this impairment can be improved by surgery [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen studies were included in the analysis [6,10,11,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. The sample size ranged from 20 to 103 and comprised 649 cases of MFACs that were treated by microscopic or endoscopic fenestration.…”
Section: Complications In the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it carries many risks such as obstruction, infection and overdrainage. Cyst fenestration using either microsurgical or endoscopic technique decreases CSF pressure within the cyst and allows brain expansion especially in young children [12][13][14][15]. Microsurgical technique may also help larger cyst wall removal in association with fenestration [16].…”
Section: Discussionmentioning
confidence: 99%